2016
DOI: 10.1111/eos.12263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of desensitizing agents on the microtensile bond strength of two‐step etch‐and‐rinse adhesives to dentin

Abstract: Desensitizers can be used to control postoperative sensitivity in adhesive restorations. The aim of this study was to evaluate the effect of desensitizing agents on the bond strength of two-step etch-and-rinse adhesive systems to dentin. Forty-two human molars were sectioned to obtain 3-mm-thick dentin discs. The discs were divided into three groups (n = 14 in each) - no-treatment control group (CT), and oxalic acid [BisBlock (BB)] and calcium phosphate [Desensibilize Nano-P (NP)] desensitizers - before the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…Furthermore, Cortiano et al. showed that OX reduced bond strength when used with the etch‐and‐rinse adhesive, but did not have any effect on SP . However, Sailer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cortiano et al. showed that OX reduced bond strength when used with the etch‐and‐rinse adhesive, but did not have any effect on SP . However, Sailer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some conditions like periodontal disease, gingival recession, abrasion, caries, and the development of non-carious cervical lesions may result in exposed dentin 4,5 . Dentin hypersensitivity arises from the application of an exogenous stimulus (chemical, mechanical, evaporative or thermal) on the exposed dentin surface 1,2,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The desensitizing agents could reduce the dentin hypersensibility using two mechanisms: by the depolarization of nerve fibers with an immediate effect and by the gradual occlusion of the tubules reducing the pain after several applications 7 . In recent years, desensitizers have been used in combination with adhesive systems in most adhesive restorative procedures.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,6 Bu gibi durumlarda diğer tedavi yöntemleri nedeniyle tıkanan dentin tübülleri, kompozit rezinlerin dentine bağlanma kuvvetini düşürebilmektedir. [7][8][9] Bu araştırmanın amacı, iki farklı hassasiyet giderici diş macununun, kompozit rezin ve cam iyonomer restoratif materyallerin kron ve kök dentinine makaslama bağlanma dayanımı (MBD) üzerine etkilerini değerlendirmektir.…”
Section: Introductionunclassified